2014
DOI: 10.1073/pnas.1405032111
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy protects C. elegans against necrosis during Pseudomonas aeruginosa infection

Abstract: Autophagy, a conserved pathway that delivers intracellular materials into lysosomes for degradation, is involved in development, aging, and a variety of diseases. Accumulating evidence demonstrates that autophagy plays a protective role against infectious diseases by diminishing intracellular pathogens, including bacteria, viruses, and parasites. However, the mechanism by which autophagy regulates innate immunity remains largely unknown. Here, we show that autophagy is involved in host defense against a pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 55 publications
2
49
0
Order By: Relevance
“…Even though we have shown that the p38 MAPK pathway and the let-7 targets lin-41 and hbl-1 are required for this phenotype, it is also possible that additional downstream stress response effectors, such as skn-1 (27), could mediate the regulation for pathogen resistance by let-7-Fam miRNAs. Predicted targets of let-7-Fam miRNAs include components of several pathways involved in pathogen resistance, including the p38 MAPK pathway, the unfolded protein response pathway, the oxidative stress response pathway, and the autophagy pathway (27,32,48,49). We propose that let-7-Fam miRNAs could function during normal, unstressed development to dampen several stress response pathways, and that under stress conditions, such as P. aeruginosa infection, the down-regulation of let-7-Fam miRNA activity reported here would broadly augment the worm's stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we have shown that the p38 MAPK pathway and the let-7 targets lin-41 and hbl-1 are required for this phenotype, it is also possible that additional downstream stress response effectors, such as skn-1 (27), could mediate the regulation for pathogen resistance by let-7-Fam miRNAs. Predicted targets of let-7-Fam miRNAs include components of several pathways involved in pathogen resistance, including the p38 MAPK pathway, the unfolded protein response pathway, the oxidative stress response pathway, and the autophagy pathway (27,32,48,49). We propose that let-7-Fam miRNAs could function during normal, unstressed development to dampen several stress response pathways, and that under stress conditions, such as P. aeruginosa infection, the down-regulation of let-7-Fam miRNA activity reported here would broadly augment the worm's stress response.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found a similar role for TFEB-1 in response to S. aureus infections in mammalian cells. An unusual role for autophagy in defense was shown by Zou et al, who demonstrated that autophagy activation prevents necrosis, and provides defense against P. aeruginosa infection [57]. Interestingly, autophagy did not reduce pathogen load (i.e.…”
Section: Autophagy Mediates Defense Against a Broad Range Of Pathogenmentioning
confidence: 99%
“…The impact autophagy has on human health and disease are far and wide, with reports demonstrating important functions in bacterial 1 and viral infections, 2 suppression of inflammation, 3 adaptive immune responses 4 and immunosurveillance, 5 neurodegeneration, 6 heart disease 7 and cancer. 8 Aberrant autophagic activity is an emerging hallmark of cancer, 9 serving a critical function in the pathogenesis, survival and response to therapy in a growing number of cancers.…”
Section: Introductionmentioning
confidence: 99%